Effects of the consumption of algal biomass versus protein concentrate on postprandial satiety and metabolism - Jia Yee Wu; Rachel Tso; Yi Ning Yong; Susanna Poh Suan Lim; Thomas Wheeler; Arup Nag; Lirong Cheng; Md. Mahabubur Rahman Talukder; Lee Huffman; Siew Young Quek; Melvin Khee Shing Leow; Sumanto Haldar (Future Foods)
Algae are promising sources of nutritious and sustainable protein, but little is known about their metabolic health impact and acceptability as meal ingredients. This acute, randomized, controlled, five-way crossover trial compared whole algal biomasses and their corresponding protein concentrates to soy protein concentrate in terms of palatability, appetite, satiety, and metabolic response. Nineteen healthy Chinese males (21–50 years, 18.5–25.0 kg/m2) consumed noodle meals supplemented with 10 g of nori biomass/protein concentrate (NB/NC), Chlorella vulgaris biomass/protein concentrate (CB/CC) or soy protein concentrate control (CON) in randomized order. At regular intervals, blood samples were collected to measure biochemical markers, while gastrointestinal tolerance, palatability, and appetite were assessed using questionnaires and visual analog scales (VAS). Results indicated that algae-enriched meals were well-tolerated and comparable to soy in both visual appeal and smell, with NB and CC outperforming soy in aftertaste (p < 0.05). There were no significant differences between treatments in glucose, insulin, C-peptide, appetite/satiety, plasma ghrelin, and GLP-1. However, exploratory analysis of serum triglycerides revealed significant time × treatment effects (p < 0.004) and differences in incremental area under the curve (iAUC0–120, p = 0.0249). Our findings reveal that algal biomasses and protein concentrates are as comparable to soy protein concentrate in palatability, satiety, and metabolic outcomes, highlighting their potential as practical, sustainable, and nutritious ingredients.